CRIMINAL LEGAL ANALYSIS OF THE CRIME OF «CRUELTY TO ANIMALS» (ART. 299 OF THE CRIMINAL CODE OF UKRAINE) - Maistro, Diana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: conducting a scientific study of the elements of the crime, provided for in the disposition of Art. 299 of the Criminal Code of Ukraine. Research methods: a set of general and special methods of scientific knowledge – terminological, logical-semantic, functional, systemic-structural, logical-normative. Results: the author analyzed the legal composition of the crime, which is provided for in the disposition of Art. 299 «Cruel treatment of animals» of the Criminal Code of Ukraine. From 8 November 2021, Art. 299 «Cruel treatment of animals» of the Criminal Code of Ukraine is set out in the new edition. In the current classification of criminal offenses, this act acquired the meaning of a crime (Parts 1, 2 of Article 299 of the Criminal Code of Ukraine – a minor crime; Parts 3, 4 of Article 299 of the Criminal Code of Ukraine – a serious crime) and the objective side of the composition of the crime against animals was expanded , as the Law of Ukraine «On Amendments to Certain Legislative Acts of Ukraine Regarding the Implementation of the Provisions of Certain International Agreements and Directives of the European Union in the Field of Animal and Plant Protection» dated July 15, 2021 No. 1684-IX. Discussion: the article examines objective and subjective features of the composition of the crime provided for in the disposition of Art. 299 of the Criminal Code of Ukraine, their content and features are described. The objective side of the specified composition of the crime has undergone significant changes, now it is expressed in 5 forms: 1) in cruel treatment of animals belonging to vertebrates, including homeless animals; 2) in violation of the rules of animal transportation, if such actions led to physical injuries, mutilation or death of the animal; 3) in harassing animals against each other, committed for hooligan or selfish motives; 4) propaganda, public appeals to commit actions that have signs of cruelty to animals; 5) distribution of materials calling for such actions.